2014
DOI: 10.3402/ejpt.v5.22969
|View full text |Cite
|
Sign up to set email alerts
|

Rape-related symptoms in adolescents: short- and long-term outcome after cognitive behavior group therapy

Abstract: BackgroundEfficacy studies on treatment in adolescent victims of single rape are lacking, even though sexual victimization is most likely to occur during adolescence and despite the fact that adolescents are at risk to develop subsequent posttraumatic stress disorder.AimThe aim of this prospective observational study was to evaluate the short- and long-term outcomes of a nine-session cognitive behavior group therapy (STEPS), including a parallel six-session parents’ group on rape-related symptomatology in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…By far, the most notable finding was the significantly more frequent levels of severe psychological distress, severe depression and anxiety symptoms and higher rates of probable PTSD and self-reported suicidal thoughts noted amongst the enslaved group compared with the non-enslaved group. While the finding of higher rates of mental health disorders amongst those enslaved, of and in itself, is not surprising given the significant literature on the psychological sequalae of sexual assault, rape and torture [ 10 ], it is the first study to examine such rates in psychiatric treatment naïve participants, and thus revealing the true impact of such experiences. Our finding of that over 90% of formerly enslaved Yazidi females had probable PTSD is well above previously reported rates of 57% [ 14 ] but consistent with others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By far, the most notable finding was the significantly more frequent levels of severe psychological distress, severe depression and anxiety symptoms and higher rates of probable PTSD and self-reported suicidal thoughts noted amongst the enslaved group compared with the non-enslaved group. While the finding of higher rates of mental health disorders amongst those enslaved, of and in itself, is not surprising given the significant literature on the psychological sequalae of sexual assault, rape and torture [ 10 ], it is the first study to examine such rates in psychiatric treatment naïve participants, and thus revealing the true impact of such experiences. Our finding of that over 90% of formerly enslaved Yazidi females had probable PTSD is well above previously reported rates of 57% [ 14 ] but consistent with others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has shown that survivors of multiple traumas exhibit more higher rates and greater severity of posttraumatic stress disorder (PTSD) [ 9 ] and that victims of recurrent sexual assaults, such as was the case of ISIS slavery experiences can lead to development of severe levels of PTSD symptoms [ 9 ]. Indeed, the experience of rape and sexual violence have shown to be associated with serious mental health disorders [ 10 ]. The victims are more likely to suffer from PTSD and major depressive disorder (MDD) [ 11 ] with other sequalae including are other anxiety disorders, sexual dysfunction, dissociative disorders, and suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies (7 out of 12) were uncontrolled pre-post treatment trials. Some were based on trauma-focused CBT [55][56][57] while others applied sequenced-based therapies that also included enhancement of specific emotion regulation strategies [58][59][60]. Studies from both approaches demonstrated improvements in emotion regulation, and in PTSD symptoms, but the absence of a control group in the studies limits interpretation of their results and the comparison between the effect sizes of the interventions.…”
Section: Emotion Regulation Difficulties and Ptsd Treatmentmentioning
confidence: 99%
“…Sexual assault is a major risk factor to develop posttraumatic stress disorder (PTSD) in both male and female populations . Sexual assault is associated with devastating psychological and physical health outcomes , including increased at‐risk behaviour .…”
Section: Introductionmentioning
confidence: 99%